Analisis Alternatif Kabijakan dalam Peningkatan Produksi Padi di Provinsi Daerah Istimewa Yogyakarta - Budi Martono (Magister Administrasi Publik, 2000)
Agriculture has been supporting economic development. Eventhough the effects of the 1997 drought in most parts of the country and tremendous dislocations caused by the crisis, the agriculture sector demonstrated tremendous resilience in coping with the economic crisis.. Based on the experienced, agriculture development policies could be done in order that agriculture sector to play a central role in the national economic recovery and repositioning agriculture as an engine ofeconomic growth and empowering farmers to articulated their aspiration and interest effectively. The problems identification showed that the causes of rice production decreasing for Yogyakarta Special Province were: (1) Paddy field contraction; (2) Productivity decreasing; (3) Low in educational back ground of the farmers ; (4) Decreasing to motivation of young generation to work in agriculture and (5) Land ownership constriction.